2007
DOI: 10.1097/01.ccm.0000281472.47067.45
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant “fortification” by topical inhibition of nuclear factor-κB activity in a newborn piglet lavage model*

Abstract: Supplementation of exogenous surfactant with a NF-[kappa]B inhibitor to create a "fortified" surfactant improves gas exchange, lung function, and pulmonary edema during 24 hrs of mechanical ventilation, without a secondary functional relapse. Inhibition of NF-[kappa]B suppressed acid sphingomyelinase activity and ceramide generation, indicating a novel proinflammatory link of NF-[kappa]B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…Furthermore, the many separate routes of administration used to deliver the NBD (including i.p., i.v., topical, intranasal, intracranial) demonstrate that it can function systemically and reach distant tissue sites although the precise pharmacokinetics remain to be determined [57]. Finally, several reports have demonstrated that the NBD peptide blocks inXammation in large animal models of disease including a piglet model of acute respiratory distress syndrome [66][67][68]. This therefore supports the exciting promise that this approach holds for possible future translational studies in the clinic.…”
Section: The Nemo Binding Domain Peptidementioning
confidence: 71%
“…Furthermore, the many separate routes of administration used to deliver the NBD (including i.p., i.v., topical, intranasal, intracranial) demonstrate that it can function systemically and reach distant tissue sites although the precise pharmacokinetics remain to be determined [57]. Finally, several reports have demonstrated that the NBD peptide blocks inXammation in large animal models of disease including a piglet model of acute respiratory distress syndrome [66][67][68]. This therefore supports the exciting promise that this approach holds for possible future translational studies in the clinic.…”
Section: The Nemo Binding Domain Peptidementioning
confidence: 71%
“…More recently, Chapoval et al showed that the peptide reduced IL-13-induced tissue inflammation, fibrosis and alveolar remodeling in an IL-13-transgenic mouse model of asthma [168]. In separate studies, topical nasal administration of the NBD peptide in piglets inhibited severe inflammation induced by repeated airway lavage [169, 170]. In this model of acute respiratory distress syndrome the peptide significantly reduced lung edema, protein content in the epithelial lining fluid, PMN accumulation and leukotriene B4 levels and improved the functional residual capacity, alveolar volume and lung mechanics [169, 170].…”
Section: Introductionmentioning
confidence: 99%
“…In separate studies, topical nasal administration of the NBD peptide in piglets inhibited severe inflammation induced by repeated airway lavage [169, 170]. In this model of acute respiratory distress syndrome the peptide significantly reduced lung edema, protein content in the epithelial lining fluid, PMN accumulation and leukotriene B4 levels and improved the functional residual capacity, alveolar volume and lung mechanics [169, 170]. Importantly, in addition to verifying the ability of the NBD peptide to ameliorate lung inflammation, these studies are the first to establish its efficacy in large animal models of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Myeloperoxidase, an enzyme present in leukocytes, is an index of tissue immune cell infiltration and was determined in ischemic and non-ischemic myocardial tissue samples as previously described [13].…”
Section: Methodsmentioning
confidence: 99%